Changes in breathing, electrocortical and muscle activity in unanaesthetized fetal lambs with age. - Clewlow, F (1983)
Electrocortical and electro-ocular activity, breathing movements and nuchal muscle activity were recorded continuously in the unanaesthetized lamb in utero (95-135 days). Electrocortical activity was recorded simultaneously from various sites. The bi-parietal electrocorticogram gave the clearest differentiation between high- and low-voltage activity. The onset of cortical differentiation from 110 days gestation was attributed to the superimposition of high-voltage electrocortical activity at 3-10 Hz on existing low-voltage activity. Three distinct patterns in the relationships between electrocortical activity, ocular activity breathing movements and nuchal muscle activity were observed at 95-106, 107-114 and 120-135 days. Isocapnic hypoxia caused a diminution in fetal breathing from 95-135 days gestation, quantitatively greater near term. After cortical differentiation, hypoxia caused the appearance of high-voltage activity within 4 min, if low-voltage electrocortical activity was present initially. The relationship, changing with age, between electrocortical activity, breathing movements, ocular and nuchal muscle activity is discussed.